자기 공진 기반의 무선전력전송 시스템에서 송수신 공진기의 구조 차이에 따른 달성 가능한 효율 비교 - 이기송(Kisong Lee); 양해권(Haekwon Yang); 나인호(In-Ho Ra) (한국정보통신학회논문지, 2017)
In magnetic resonance-based wireless power transfer (WPT) systems, frequency splitting phenomenon, in which power transfer efficiency (PTE) decreases seriously as resonators are close to each other, is the problem that we should address for reliable power transfer in short distance. In this paper, we present WPT systems using an equivalent circuit model and analyze PTE and marginal coupling coefficient ($k_{split}$) where the frequency splitting occurs. In addition, we perform circuit-level simulations using Advanced Design System, and show that the achievable PTE is different for the structures of resonators when k>$k_{split}$. We confirm that higher PTE can be ensured as k increases in the case of identical resonators, while PTE is degraded as k increases in the case of non-identical resonators. Therefore, in short distance, in which k>$k_{split}$, it is more efficient for achieving reliable PTE to use identical resonators rather than non-identical resonators. 자기 공진 기반의 무선전력전송 시스템에서, 송수신 공진기가 가까워짐에 따라 전력비 효율이 급격히 감소하는 주파수 스플리팅 현상은 근거리에서 안정적인 전력 전송을 위하여 반드시 해결해야 하는 문제이다. 본 논문에서는 등가회로 모델을 이용하여 무선전력전송 시스템을 모델링하고, 전력비 효율 및 주파수 스플리팅이 발생하는 한계 커플링 계수($k_{split}$)를 도출하였다. 또한, Advanced Design System을 이용하여 회로 수준의 시뮬레이션을 수행하였으며, 이를 통해 k>$k_{split}$ 의 환경에서 송수신 공진기의 구조에 따라 달성 가능한 전력비 효율이 다름을 보였다. 동일한 구조의 공진기의 경우 k가 커지더라도 높은 수준의 전력비 효율을 유지하는 반면, 상이한 구조의 공진기의 경우 k가 커짐에 따라 전력비 효율도 감소함을 확인했다. 그러므로 k>$k_{split}$를 만족하는 근거리 환경에서 안정적인 전력비 효율을 달성하기 위해서는 상이한 구조의 공진기보다는 동일한 구조의 공진기를 사용하는 것이 더 효율적이다.